2021
DOI: 10.1177/10848223211035320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on High-risk Neonate Home Care Program: An Audit Study

Abstract: One of the most important goals of the health system in this pandemic was to provide a home care for the high-risk neonates. The aim of this study was to audit a high-risk neonate home care program during the COVID-19 pandemic. This descriptive-analytical study was conducted with the participation of 158 high-risk neonates discharged from neonatal intensive care units of hospitals. Data collection was performed through questionnaire and a researcher-made checklist. The researcher observed and evaluated 7 areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In addition, from the nurses' point of view, about 80% of physician's resist home care and it is emphasized that with an inter-professional approach and the cooperation of health team members such as nurses, physiotherapists, and occupational therapists regular visits are made to maximize the effectiveness of home care. 16,23 The researchers' experiences and the results of some other studies in Iranian cities also showed that the lack of coordination between professions is one of the main problems in home care and many nurses and doctors are reluctant to go home-visits and therefore this problem is due to lack of cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, from the nurses' point of view, about 80% of physician's resist home care and it is emphasized that with an inter-professional approach and the cooperation of health team members such as nurses, physiotherapists, and occupational therapists regular visits are made to maximize the effectiveness of home care. 16,23 The researchers' experiences and the results of some other studies in Iranian cities also showed that the lack of coordination between professions is one of the main problems in home care and many nurses and doctors are reluctant to go home-visits and therefore this problem is due to lack of cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Namun, beberapa evaluasi dan peninjauan rutin perlu dilakukan pada instruksi dan implementasi. Perawatan di rumah selama pandemi COVID-19 dilaksanakan melalui telepon dan tindak lanjut (Ansari et al, 2021).…”
Section: A Pendahuluanunclassified
“…Another fact of the event is the increase in the demand for receiving home care, which was caused by restrictions on leaving the house, fear of going to medical centers, and hospitalization. 5…”
Section: Introductionmentioning
confidence: 99%
“…13 Then, the conformity degree of implementing the nursing care program at home for the high-risk infants with the existing standards was studied, and the impact of COVID-19 on the implementation of the program was investigated. 5 In the way of completing the findings and considering the fact that the attitude of care recipients is effective in accepting the service and improving its implementation. The present study aims to investigate the infant family (mother and father) attitude toward the infant home-based care program amid the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%